Designing a DNA Vaccine-based Leishmania major Polytope (Preliminary Report) - JEIBOUEI, Shabnam (Iran J Parasitol, 2017)
BACKGROUND: Leishmaniasis is a neglected disease affecting millions of people worldwide. The treatment of the disease is hampered due to high cost, toxicity and the crisis of drug resistance. Polytope approaches of genetic immunization could be a strategy for prevention of infectious diseases. Furthermore, the identification of Leishmania genome sequence and the application of bioinformatics assist us to devise an effective vaccine’s candidate. METHODS: A linear sequence from predicted epitopes of GP63, LACK and CPC antigens was designed and was optimized using online available algorithms. The synthesized sequence (LAKJB93) was ligated to pEGFP-N1 plasmid. RESULTS: The 264bp sequence was cloned at N terminal of GFP into pEGFP_N1 expression vector and transfect into CHO cell line. Construct was efficient expressed in CHO cells. CONCLUSION: The protein of LAKJB93 cosnstruct was expressed in CHO cells successfully.